To Raise Awareness of Higher Education Students about the Development of Vocal Pedagogy through the Science of Vocals and Modern Music - Boychayeva Nazbuvi Avazovna (Researchparks Publishing, 2022)
In ancient times, singing had a folk and religious character and did not require didactic training. Accompanied by musical instruments, they sang